STRENGTHENING MATHEMATICS AND NATURAL SCIENCES EDUCATION BASED ON THE LOCAL WISDOM OF SOUTH NIAS: INTEGRATION OF TRADITIONAL CONCEPTS IN MODERN EDUCATION - Harefa, Darmawan (Haga : Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service aims to strengthen the teaching of mathematics and natural sciences (Science) in schools in South Nias through the integration of local wisdom values. With a cultural-based approach, this service focuses on developing teaching methods that not only introduce scientific concepts but also connect the lessons to students' experiences, traditions, and local customs. The activities involve teachers and students in the development of learning media based on local wisdom, teacher training, and the implementation of project-based learning models. The results of this service show that the integration of local wisdom in teaching enhances students' understanding of mathematical and science concepts, strengthens their motivation to learn, and preserves local cultural values. Additionally, teachers acquired new skills in developing contextual and creative teaching methods. This service makes a positive contribution to both the preservation of culture and the development of education that is more relevant to the local context.